2016
DOI: 10.1111/ecog.02293
|View full text |Cite
|
Sign up to set email alerts
|

Isolation drives taxonomic and functional nestedness in tropical reef fish faunas

Abstract: Taxonomic nestedness, the degree to which the taxonomic composition of species‐poor assemblages represents a subset of richer sites, commonly occurs in habitat fragments and islands differing in size and isolation from a source pool. However, species are not ecologically equivalent and the extent to which nestedness is observed in terms of functional trait composition of assemblages still remains poorly known. Here, using an extensive database on the functional traits and the distributions of 6316 tropical ree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
77
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 76 publications
(152 reference statements)
9
77
0
Order By: Relevance
“…Using a different approach based on paired overlap and matrix filling to quantify nestedness per se, other studies reported patterns consistent with our results (Henriques-Silva et al 2013, Bender et al 2016. In another example, Bender et al (2016) found that spatial isolation is an important driver of functional and taxonomic nestedness. In another example, Bender et al (2016) found that spatial isolation is an important driver of functional and taxonomic nestedness.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Using a different approach based on paired overlap and matrix filling to quantify nestedness per se, other studies reported patterns consistent with our results (Henriques-Silva et al 2013, Bender et al 2016. In another example, Bender et al (2016) found that spatial isolation is an important driver of functional and taxonomic nestedness. In another example, Bender et al (2016) found that spatial isolation is an important driver of functional and taxonomic nestedness.…”
Section: Discussionsupporting
confidence: 90%
“…At a biogeographic scale, reduced landscape connectivity likely promotes long-term evolutionary processes such as speciation and extinction, which might eventually result in large-scale turnover patterns due to differences in regional species pools (Leprieur et al 2011). Using a different approach based on paired overlap and matrix filling to quantify nestedness per se, other studies reported patterns consistent with our results (Henriques-Silva et al 2013, Bender et al 2016. Using a different approach based on paired overlap and matrix filling to quantify nestedness per se, other studies reported patterns consistent with our results (Henriques-Silva et al 2013, Bender et al 2016.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…that spatial isolation among habitat patches increases nestedness (Bender et al 2017, Gianuca et al 2017. Similar results have been found in empirical studies showing e.g.…”
Section: Discussionsupporting
confidence: 88%
“…reciprocal monophyly of oceanic lineages); pattern II.2, detection of cryptic lineages alternatively sorted between the Indian and Pacific oceans but displaying geographic paraphyly (i.e. more than 2 lineages); pattern III, species are either paraphyletic or polyphyletic cies with Indo-Pacific or pan-Pacific distribution has been predominantly affected by geographic isolation, a result previously suggested by recent phylogenetic and biogeographic studies (Hubert et al 2011, Quenouille et al 2011, Pellissier et al 2014, Bender et al 2017. For instance, genetic divergence was higher between sites located in different oceans than between sites within the western Pacific Ocean.…”
Section: Geographic Isolation and Population Fragmentationmentioning
confidence: 74%